Interlaboratory reproducibility of a test method following 4-field test methodology to evaluate the susceptibility of Clostridium difficile spores. Issue 1 (September 2019) - Gemein, S.; Gebel, J.; Christiansen, B.; Martiny, H.; Vossebein, L.; Brill, F.H.H.; Decius, M.; Eggers, M.; Koburger-Janssen, T.; Meckel, M.; Werner, S.; Hunsinger, B.; et al.
Summary: Background: Sporicidal surface disinfection is recommended to control transmission of Clostridium difficile in healthcare facilities. EN 17126 provides a method to determine the sporicidal activity in suspension and has been approved as a European standard. In addition, a sporicidal surface test has been proposed. Aim: To determine the interlaboratory reproducibility of a test method for evaluating the susceptibility of a C. difficile spore preparation to a biocidal formulation following the 4-field test (EN 16615 methodology). Methods: Nine laboratories participated. C. difficile NCTC 13366 spores were used. Glutaraldehyde (1% and 6%; 15 min) and peracetic acid (PAA; 0.01% and 0.04%; 15 min) were used to determine the spores' susceptibility in suspension in triplicate. Findings: One-percent glutaraldehyde revealed a mean decimal log10 reduction of 1.03 with variable results in the nine laboratories (0.37–1.49) and a reproducibility of 0.38. The effect of 6% glutaraldehyde was stronger (mean: 2.05; range: 0.96–4.29; reproducibility: 0.86). PAA revealed similar results. An exemplary biocidal formulation based on 5% PAA was used at 0.5% (non-effective concentration) and 4% (effective concentration) to determine the sporicidal efficacy (4-field test) under clean conditions in triplicate with a contact time of 15 min. When used at 0.5% it demonstrated an overall log10 reduction of 2.68 (range: 2.35–3.57) and at 4% of 4.61 (range: 3.82–5.71). The residual contamination on the three primarily uncontaminated test fields was <50 cfu/25 cm 2 in one out of nine laboratories (0.5%) and in seven out of nine laboratories (4%). Conclusion: The interlaboratory reproducibility seems to be robust.